Advances in Flexible and Wearable Energy‐Storage Textiles. Issue 11 (29th July 2018) - Liu, Zhuoxin; Mo, Funian; Li, Hongfei; Zhu, Minshen; Wang, Zifeng; Liang, Guojin; Zhi, Chunyi
Abstract: Considerable attention has been drawn to flexible and wearable energy‐storage devices due to the blooming of portable and wearable electronics in recent years. However, huge challenges are yet to be addressed before the need of both high flexibility and high performance can be met. With many desired features for wearable applications, textiles have become a growing research frontier where scientific views from various fields collide, sparking new ideas. Here, recent research progress in energy‐storage textiles (ESTs), in which textiles are employed to enhance either electrochemical performance or flexibility and wearability, is summarized. The research of ESTs is mainly divided into three parts, with a focus on supercapacitors, lithium‐ion batteries (LIBs), and some other representative battery systems, respectively. Electrode preparation, cell assembly, device performance, and the remaining challenges are discussed in detail, aiming to provide insights for future development. Abstract : Energy‐storage textiles have received tremendous attention due to their advantages in wearable applications. An overview of current designs of energy‐storage textiles is presented, with focus on supercapacitors, lithium‐ion batteries, and some other promising battery systems. Electrode fabrication, cell assembly, device performance, and flexibility demonstration, for example, are discussed. Challenges and perspectives of future development are also considered.